2004
DOI: 10.1111/j.1468-2982.2003.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related and Condition-Specific Quality of Life in Episodic Cluster Headache

Abstract: Health-related quality of life was studied in 35 episodic cluster headache (CH) patients during and after the cluster period, using a generic (SF-36) and a headache-specific (MSQ2.1) instrument. The results were compared with those of age- and sex-matched migraineurs (n = 53) and healthy persons (n = 62). During the cluster period patients had lower scores than controls in all SF-36 and MSQ2.1 domains. The difference was significant for most SF-36 and all MSQ2.1 domains. Although CH patients had lower scores t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 27 publications
3
45
2
2
Order By: Relevance
“…In CH, assessment of QoL is currently limited to use of generic scales, such as the SF-36, and headache disability instruments, which have shown significantly diminished scores compared to headache-free controls [2, 5, 7, 16, 21]. Moreover, a study found significant differences between CH patients in the ictal versus the interictal period, but no significant differences between CH patients and migraineurs [7]. The authors postulated that since the study used a migraine-specific measure, it might not have been able to truly capture the essential aspects of CH [7].…”
Section: Introductionmentioning
confidence: 99%
“…In CH, assessment of QoL is currently limited to use of generic scales, such as the SF-36, and headache disability instruments, which have shown significantly diminished scores compared to headache-free controls [2, 5, 7, 16, 21]. Moreover, a study found significant differences between CH patients in the ictal versus the interictal period, but no significant differences between CH patients and migraineurs [7]. The authors postulated that since the study used a migraine-specific measure, it might not have been able to truly capture the essential aspects of CH [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a clinically effective therapy is not necessarily reflected by an improvement of the QOL scores of migraineurs (32). Patients may also feel that the instruments do not capture some important areas of their QOL, as was the case of our patients (suffering from cluster headache or migraine) during the above-mentioned trial (14).…”
Section: Introductionmentioning
confidence: 99%
“…MSQ2.1 was found to be a reliable and valid means of assessing QOL in migraine and has been formally validated for patients undergoing prophylactic migraine treatment (13). It has also been used in cluster headache (14). Recently, MSQ2.1 was validated for clinical use in episodic and chronic migraine (15) and was found to demonstrate significant differences between these, with chronic migraine sufferers having lower values in all dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-related quality of life is significantly impaired in CH suf ferers. 4,5 Even though it is under-recognised and often suboptimally managed in primary care, 6,7 an early diagnosis and prompt treatment are essential to alleviate the devastating morbidity of these attacks. 8…”
mentioning
confidence: 99%